University Spin-Off: A Literature Review for Their Application in Colombia - CASTRILLÓN MUÑOZ, Andrés José; MORO, Alfonso Infante; COLLAZOS, Alexander Zúñiga; LÓPEZ, Francisco José Martínez (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
This article gathers some of the most important theoretical and conceptual references, systematized from the review and consultation of specialized literature on university Spin Off, through a documentary type methodological qualitative process with a tendency to observe closely, afterwards, the capacity that has the University of Cauca, a public Colombian higher education institution, regarding the organization of knowledge to transfer the results generated by its research groups towards the environment, in alliance with entrepreneurs and other groups of interest, where the following analytical categories among others, are highlighted: The evaluation of the diverse typologies presented by well-known experts based on their heterogeneity. The analysis of different organizational models related to this type of entrepreneurships. The factors of success and the failure of some universities Spin Offs. The stages that might have to be exhausted for the successful implementation of this kind of organizations and the basic aspects to be considered in the relationship between University-Firm-State. As closure, it is suggested that for all legal purposes, a university Spin-Off in Colombia is "a company based on knowledge, especially the one protected by rights of Intellectual Property, created in the area of the Higher Education Institution (HEI), as a result of research and development activities conducted under their support, in their laboratories and facilities or by researchers who are linked to them, among others" (Law 1838, Act of 2017).